The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.3390/antibiotics13010066
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Streptococcus pneumoniae before and after the Introduction of Pneumococcal Conjugate Vaccines in Brazil: A Systematic Review

Patricia Alice Knupp-Pereira,
Amanda Seabra Cabral,
Ítalo Moraes Dolores
et al.

Abstract: Streptococcus pneumoniae causes serious illnesses, such as pneumonia, bacteremia, and meningitis, mainly in immunocompromised individuals and those of extreme ages. Currently, pneumococcal conjugate vaccines (PCVs) are the best allies against pneumococcal diseases. In Brazil, the 10-valent and 13-valent PCVs have been available since 2010, but the threat of antimicrobial resistance persists and has been changing over time. We conducted a systematic review of the literature with works published since 2000, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Faced with this situation, since 2010, Brazil has introduced restrictions for over-the-counter sales of antimicrobials, determining that sales should be associated with the presentation and retention of a medical prescription, promoting control over the use of these products in the country [ 38 ]. This measure, associated with the introduction of PCVs, which contained the prevalent serotypes associated with the antimicrobial resistance causing the IPD in question, resulted in an initial reduction in the non-susceptibility rates to antimicrobials, mainly to beta-lactams, used for the treatment of pneumococcal infections [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faced with this situation, since 2010, Brazil has introduced restrictions for over-the-counter sales of antimicrobials, determining that sales should be associated with the presentation and retention of a medical prescription, promoting control over the use of these products in the country [ 38 ]. This measure, associated with the introduction of PCVs, which contained the prevalent serotypes associated with the antimicrobial resistance causing the IPD in question, resulted in an initial reduction in the non-susceptibility rates to antimicrobials, mainly to beta-lactams, used for the treatment of pneumococcal infections [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies evaluating the long-term impact of the use of PCV10 on antimicrobial resistance have demonstrated that the benefit of controlling antimicrobial resistance has impacted by pneumococcal infections caused by non-PCV10 serotypes associated with antimicrobial resistance, mainly serotypes 19A and 6C [ 25 , 30 , 31 , 39 , 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%